A new Ophidion (Orchidaceae, Pleurothallidinae) from the Pacific lowlands of Colombia and the unresolved phylogenetic position of Phloeophila s.l. Issue 1 (31st December 2023) - Reina-Rodríguez, Guillermo A.; Bogarín, Diego; Hernandez, Yerlin; Nicholls-Giraldo, Isabel; Pérez-Escobar, Oscar A.
Abstract : A species new to science of a miniature orchid, endemic to the humid Pacific lowland, Municipality of Buenaventura (Valle del Cauca, Colombia), is described and illustrated. Ophidion erectilabrum sp. nov. is morphologically similar to O. alphonsianum, but the new species is recognized by the orbicular leaves (vs. elliptic), the erect inflorescence, longer than the leaves (vs. descending, shorter than the leaves), and the abruptly upward curved epichile (vs. flat). Because of the different proposals in the circumscription of Phloeophila s.l., we performed a new phylogenetic analysis to assess the most appropriate genus to place the new species, and discuss the phylogenetic position of Luerella, Ophidion, and Phloeophila based on all currently available data from nrITS and mat K and recent studies using high-throughput sequencing. Although the three genera are supported as monophyletic groups, we recovered unresolved relationships and discordant topologies among them using only these two molecular markers. Therefore, we describe this species in Ophidion because of the morphological differences between Luerella and Phloeophila and because the grouping of Phloeophila s.l. lacks diagnostic features, and is yet to be supported by molecular analysis.